Source Of Economic Growth In Libya (1970-2014): A Case Of Oil-based Economy - Taloba, Abdelatif Aissa (جامعة الوادي- University of Eloued, 2016)
Economic growth in Libya during 1970 to 2014 can be explained more by capital accumulation rather than labour or TFP. TFP contribution to growth was insignificant. A lower share of labour in GDP means that it was also less important than capital in determining the growth rate of Libya. Human capital also has no significant effect on economic process; decline in its productivity was observed despite some progress in in education and health services over the period of interest. Such declining productivity is an unsolved question not only in Libyan economy, but also in other oil-based MENA countries with similar features.
مقال
Keywords: Economic Growth; Oil; Technological Change